Сверхзвуковой флаттер удлиненной прямоугольной пластинки со свободным краем, сжатой по потоку газа - Мартиросян, С. Р. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
By analyzing, as an example, a thin elastic compressed elongated plate streamlined by supersonic gas flows, we study the influence of the initial stress state of the plate on the stability of the unperturbed motion of the dynamic system “plate – flow” under the assumption of presence of concentrated inertial masses and moments on its free edge. An analytical solution of the problem of stability of the unperturbed motion of a dynamical system is obtained. An exact estimate of their influence on the stability of the unperturbed motion of the system is given, depending on its "essential" parameters and the relative thickness of the plate. It is shown that the compressive forces lead to a significant decrease in the stability of the system. Ուսումնասիրված է գերձայնային գազի հոսքում սեղմված` շրջհոսման ուղղությամբ, մեկ ազատ եզրով առաձգական երկարաձիգ ուղղանկյուն սալի նախնական լարվածային վիճակի ազդեցությունը «սալ–հոսք» համակարգի ոչ խոտորված շարժման կայունության վրա: Ենթադրվում է, որ սալի ազատ եզրին առկա են կենտրոնացված իներցիոն զանգվածներ և մոմենտներ: Ստացված է կայունության խնդրի անալիտիկ լուծումը: Գնահատված է սեղմող ուժերի ապակայունացնող ազդեցությունը «սալ–հոսք» համակարգի ոչ խոտորված շարժման կայունության վրա: В статье, в линейной постановке, исследуется влияние первоначальных сжимающих сил в срединной поверхности удлинённой прямоугольной упругой пластинки с одним свободным краем, обтекаемой с одной стороны сверхзвуковым потоком газа, на устойчивость её невозмущённого состояния равновесия в предположении, что на свободном крае имеются сосредоточенные инерционные массы и моменты. Получено аналитическое решение. Показано, что первоначальные сжимающие силы приводят к понижению устойчивости системы.
Keywords: Механика